Green-Modified Ni/Al LDH with Camellia sinensis Bioactives: A Sustainable Strategy for Ceftriaxone Removal - Amri Amri; Najma Annuria Fithri; Muhammad Said; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Ceftriaxone (CEF) is a β-lactam antibiotic widely used in the medical field to treat various bacterial infections in both humans and animals. The high usage of CEF has the potential to cause environmental pollution and antimicrobial resistance, necessitating effective treatment methods. In this study, the adsorption method is proposed using Ni/Al layered double hydroxide (LDH) and Camellia sinensis extract-modified material (Ni/Al-CSe) as a sustainable bio-modification approach. The results show the optimal adsorption pH for Ni/Al LDH is 3 and for Ni/Al-CSe is 5, with the adsorption isotherms following the Freundlich model and the kinetics conforming to pseudo-first order (PFO). The maximum adsorption capacity (Qm) significantly increased from 28.818 mg.g-1 (Ni/Al LDH) to 111.111 mg.g-1 (Ni/Al-CSe). Thermodynamic analysis revealed that adsorption on both materials proceeds spontaneously, while the consistently more negative ΔG values and predominantly exothermic behavior of Ni/Al-CSe confirm its superior thermodynamic favorability associated with more specific surface interactions. Regeneration tests up to four cycles showed that Ni/Al-CSe was more stable than Ni/Al LDH. Overall, modifying Ni/Al LDH with Camellia sinensis extract was proven to enhance adsorption capacity, spontaneity, and stability, providing an effective and environmentally friendly solution for antibiotic treatment. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).